Effect of an extract of Pinus koraiensis leaves, Lycium chinense fruit, and Saururus chinensis (Lour.) Baill. leaves on liver function in excessive drinkers: A randomized, double-blind, placebo-controlled trial. (August 2021) - Park, Ju Hyun; Bok, Min Kyung; Kim, Jieun; Maeng, Sungho; Kim, Sung-Hoon; Jung, Ji Hoon; Lee, Hyo-Jung; Lim, Hyunjung
Graphical abstract: Highlights: GGT significantly decreased in the women PLC group compared with the placebo group. TC, LDL-C, and HDL-C significantly decreased in the PLC group after 12-weeks. Some item of FSS questionnaire improved in PLC group after 12-weeks. No adverse event and safety issue for 12-week intake PLC. Abstract: Chronic alcohol consumption is a major risk factor for alcoholic liver disease. In this study, we examined the effect of an extract of Pinus koraiensis leaves, Lycium chinense fruit, and Saururus chinensis (Lour.) Baill. leaves (PLC) on liver function in Korean. A randomized, double-blind, placebo-controlled study was performed in 50 excessive drinkers. The subjects were randomly assigned to PLC (n = 25, 2, 000 mg/day) or placebo (n = 25) groups. Blood liver enzymes, lipid profiles, and antioxidant enzymes were assessed at baseline and 12 weeks. GGT level significantly decreased in women in the test group compared with the placebo group (-2.50 ± 3.54 U/L vs. 3.80 ± 11.23 U/L, P = 0.006). TC (-13.04 ± 25.65 mg/dL, P = 0.020) and LDL-C (-10.33 ± 24.15 mg/dL, P = 0.047) levels reduced in the test group after 12 weeks. Although PLC, appears the possibility of improving liver function in excessive drinkers, however, a larger scale and long-term intervention study should be performed.